Journal of Borneo Kalimantan : A peered-reviewed and multidisciplinary journal on transforming communities in Borneo-Kalimantan & developing regions - Shahren, Ahmad Zaidi Adruce; Hiram, Ting; Lam, Chee Kheung; Alexandra Nastassia, John; Stephen, Donald; Dayang Siti Aisah, Abang Suhaili; Abang Mohd Heikal, Abg Othman; Adila, Latif; Robert, Clayton; Parveen, Kaur; Saidatul Nornis, Hj Mahali; Lim, Connie Keh Nie; et al. (Institute of Borneo Studies, UNIMAS, 2016)
The Journal of Borneo-Kalimantan (IJBK) is published by the Institute of Borneo Studies (IBS) formerly known as Institute of East Asean Studies (IEAS). This is an international peer reviewed open access journal with an objective to provide a platform for international scholars to publish high-quality multidisciplinary papers related to Borneo Kalimantan.